Molecular spectroscopy analysis of the substitution of bone tissue by HAp/PLLA composite biomaterial. Issue 4 (2004) - Ignjatovic Ignjatovic, Nenad Nenad; Uskokovic Uskokovic, Dragan Dragan
Abstract : Due to its pronounced osteoinductive properties, calcium hydroxyapatite (HAp) has been widely used in medicine. Bioresorptive poly-L-lactide (PLLA) as a polymer biomaterial has been also used extensively in medicine for its non-toxicity and biocompatibility. To combine the advantages exhibited by each of these materials, a HAp/PLLA composite biomaterial has been synthesized and used for reconstruction and repair of bone defects. Hydroxyapatite/poly-L-lactide (HAp/PLLA) composite biomaterial with PLLA of 50, 000 and 430, 000 g/mole molecular weight was studied in vivo . The biocomposite with PLLA of both molecular weights was implanted into mice, then removed from their organisms and analyzed by the Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM) and histopathologic analysis. Characteristic absorption bands, registered and defined by FT-IR spectroscopy, confirm the formation of new functional groups and compounds during the bone repair process using HAp/PLLA biocomposite with PLLA of 50, 000 and 430, 000 molecular weights. Analysis of the microstructures of the sample surfaces by scanning electron microscopy (SEM) before and after implantation revealed bioresorption of the PLLA polymer phase in the system with PLLA of lower molecular weight and generation of collagen fibers at the sites of implanted bioresorptive PLLA. As the studied synthetic materials behave as the natural bone, i.e., they are phagocytosed and resorpable, they can be considered as biocompatible.